Pinocembrin Inhibits the Proliferation and Metastasis of Breast Cancer via Suppression of the PI3K/AKT Signaling Pathway - Zhu, Xinbing; Li, Rongnian; Wang, Chen; Zhou, Shuo; Fan, Yujia; Ma, Shuang; Gao, Didi; Gai, Nian; Yang, Jing (Frontiers in Oncology, 2021)
The survival rate of breast cancer (BC) patients remains poor, thus the identification of safe and effective new drugs is crucial to improve therapeutic outcomes and overall survival. Pinocembrin (PCB), a pharmacologically active ingredient of Pinus heartwood, Eucalyptus, Euphorbia, Populus, and Sparattosperma leucanthum, has been widely applied for the treatment of various diseases and possesses anticancer activities. In vitro assays were performed to investigate the antiproliferation and antimetastasis activities of PCB in BC cells. A tumorigenesis assay with the use of murine BC models was performed to assess the antiproliferation activities of PCB in vivo. Moreover, the molecular mechanisms underlying the anticancer activities of PCB in BC cells were explored. The results showed that the anti-inhibitory and antiproliferation activities of PCB in BC might involve cell cycle (G2/M phase) arrest and apoptosis. PCB downregulated the expression levels of proteins involved in cell cycle progression and apoptosis, including cyclinB1, Cdc2, PARP1, Bcl-2, and survivin, and upregulated protein levels of cleaved PARP1，cleaved caspase3, cleaved caspase9, and BAX. In a murine subcutaneous tumor model, PCB suppressed the growth of MCF-7 cells in vivo. Low concentrations of PCB also significantly inhibited the migration and invasion abilities of BC cells. Mechanistically, PCB administration was correlated to suppression of the PI3K/AKT signaling pathway. Inhibition of the proliferation of BC cells by PCB involved cell cycle (G2/M phase) arrest and apoptosis in vitro and in vivo. Low concentrations of PCB also significantly inhibited the migration and invasion abilities of BC cells. These findings suggest that PCB might be an effective agent for treatment of BC patients.